Pengaruh Variasi Komposisi dan Tekanan Alat Press Mini Produk Terhadap Mechanical Properties Produk Papan Silikat Skala Mini (Studi Kasus di PT XYZ) - Bayhaqi Ilham, Aldiana; Dampang, Sarah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Silicate board is one of the products produced at PT XYZ. This material is resistant to water and fire, making it very useful in building construction. In addition, silicate board can be used as an alternative to bricks or gypsum because it is easier to apply. The manufacture of silicate board requires the right combination of compositions to suit industrial needs. This study aims to analyze the effect of variations in composition and pressure in the process of making small-scale silicate boards (mini products). Mini products are made in several samples with different combinations of composition and pressure. In the study, cement compositions were used with percentages of 30%, 32%, and 34% at each pressure. Meanwhile, the pressure applied was 60 bar and 70 bar for each composition. The analysis parameters include the Modulus of Rupture (MOR), Moisture content, Water absorption, and density values ​​in each sample. The results of the study showed fluctuations in these values ​​based on variations in composition and pressure. However, there was one sample that consistently had the highest value in various aspects. This finding indicates that the combination of composition and pressure must be adjusted properly to produce silicate boards with optimal quality.